2013
DOI: 10.1111/cns.12129
|View full text |Cite
|
Sign up to set email alerts
|

Sigma‐1 Receptor Knockout Impairs Neurogenesis in Dentate Gyrus of Adult Hippocampus Via Down‐Regulation of NMDA Receptors

Abstract: The σ1 R deficiency impairs neurogenesis in DG through down-regulation of NMDArs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 56 publications
4
46
1
Order By: Relevance
“…Thus, the lack of an anti-depressive effect by paroxetine in CaMKIV null mice suggests that Sig-1R stimulatory action rather than serotonin reuptake inhibition accounts for fluvaxamine's anti-depressive action. However, lack of amelioration by fluoxetine as reported by Sha et al [44] cannot be explained due to a low affinity for Sig-1R. Our hypothesis that fluvoxamine-induced anti-depressive action in CaMKIV null mice is mediated by Sig-1R stimulation was confirmed by the observation that the Sig-1R-specific agonist SA4503 ameliorates impaired adult hippocampal neurogenesis in DG and depressive behaviors in CaMKIV null mice.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, the lack of an anti-depressive effect by paroxetine in CaMKIV null mice suggests that Sig-1R stimulatory action rather than serotonin reuptake inhibition accounts for fluvaxamine's anti-depressive action. However, lack of amelioration by fluoxetine as reported by Sha et al [44] cannot be explained due to a low affinity for Sig-1R. Our hypothesis that fluvoxamine-induced anti-depressive action in CaMKIV null mice is mediated by Sig-1R stimulation was confirmed by the observation that the Sig-1R-specific agonist SA4503 ameliorates impaired adult hippocampal neurogenesis in DG and depressive behaviors in CaMKIV null mice.…”
Section: Discussionsupporting
confidence: 82%
“…In fact, the elevation of CaMKII activity by SA4503 was eliminated by NMDAR antagonist. The regulation of NMDAR activity by Sig-1R was also reported in Sig-1R null mice in which adult hippocampal neurogenesis is impaired via downregulation of NMDAR subunit NR2B [44]. Martina et al [54] reported that a Sig-1R agonist inhibits small-conductance calcium-activated potassium channel in the hippocampus and consequently increased Ca 2+ mobilization by an NMDAR-dependent mechanism.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…An earlier study (Yang et al, 2011) reported that σ 1 R agonist enhances the survival of newborn neurons in an NMDArdependent manner. The σ 1 R deficiency suppresses the NR2B phosphorylation leading to the dysfunction of NMDAr without the changes in membrane properties, which impairs the survival of newborn neurons in the DG (Sha et al, 2013). The density of NMDAr is lower in the brain of depressed patients compared to controls (Nudmamud-Thanoi and Reynolds, 2004;Nowak et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…A reduction of mature newborn neurons has been determined in male σ 1 R À / À mice (Sha et al, 2013). During pregnancy, the number of newborn neurons in the DG is significantly increased followed by a rapid decline after parturition (Pawluski and Galea, 2007;Furuta and Bridges, 2005).…”
Section: Introductionmentioning
confidence: 99%